Nordic Contributions in IS Research 5th Scandinavian Conference on Information Systems, SCIS 2014, Ringsted, Denmark, August 10-13, 2014, Proceedings - Commisso, Trine Hald; Nørbjerg, Jacob; Pries-Heje, Jan (Lecture Notes in Business Information Processing, 2014)
This book contains the refereed proceedings of the 5th Scandinavian Conference on Information Systems, SCIS 2014, held in Ringsted, Denmark, in August 2014. The theme for this book as well as for the conference is "Designing Human Technologies." The theme combines the interplay of people with technology-a classic theme in Scandinavian information systems research-with a growing interest within the IS research field in design and design science research. The nine papers accepted for SCIS 2014 were selected from 22 submissions.